Dietary camu camu, Myrciaria dubia, enhances immunological response in Nile tilapia - Yunis-Aguinaga, Jefferson [UNESP]; Fernandes, Dayanne C. [UNESP]; Eto, Silas F. [UNESP]; Claudiano, Gustavo S. [UNESP]; Marcusso, Paulo F. [UNESP]; Marinho-Neto, Fausto A. [UNESP]; Fernandes, João B.K. [UNESP]; de Moraes, Flávio R. [UNESP]; de Moraes, Julieta R. Engrácia [UNESP] (Elsevier, 2016)
Camu camu, Myrciaria dubia, is an Amazon plant that presents high levels of vitamin C in its composition. Several studies in animals and humans have demonstrated their efficiency in the prevention and treatment of various diseases. However, there are no reports of its properties in fish. The aim of this study was to evaluate the effect of the oral administration of the extract of this plant in the immune parameters in Nile tilapia, Oreochromis niloticus. 400 Nile tilapia (80 ± 5 g) were randomly distributed into 20 tanks with 1500 L capacity each (20 fish/tank). After a week of adaptation to environmental conditions, it was provided a diet for 5 weeks, using different levels of inclusion of camu camu extract: 0, 50, 100, 250, and 500 mg/kg of feed. Each treatment consisted of four replicates. It was obtained 40.5 mg of vitamin C/g of camu camu pulp powder by high-performance liquid chromatography. At the end of the trial period, fish were inoculated with Aeromonas hydrophila in the swim bladder. Samples were taken after 6; 24 and 48 h of the challenge. Results revealed that fish supplemented with this herb showed significant increase (P < 0.05) in white blood cells counts in blood and exudate, burst respiratory activity, lysozyme activity, serum bactericidal activity, direct agglutination, and melanomacrophage centers count. Red blood cells count, hemoglobin, hematocrit, and biochemical profile of fish supplemented with the herb presented no statistical differences compared to control group (P > 0.05). No histopathological lesions were observed in intestine, kidney, spleen, and gills. It can be concluded that the addition of Myrciaria dubia in tilapia feed improves the immune response and the growth after 5 weeks, especially, at a dose of 500 mg/kg.
Keywords: Amazon herb; Direct agglutination; Hematology; Phytotherapy; Serum bactericidal activity